Bone Mineral Density Distribution in the Posterior Wall of the Lateral Mass Evaluated by Computed Tomography Osteoabsorptiometry - Doi, Kazuma; Inoue, Nozomu; Tani, Satoshi; Mizuno, Junichi (Asian Journal of Neurosurgery, 2024)
Objective Cervical open-door laminoplasty using plates and miniscrews is gaining popularity. One of the complications of this procedure is the loosening or back-out of the miniscrews inserted in the lateral mass (LM). Bone mineral density (BMD) measured by computed tomography (CT) has been used as a predictor of bone strength. However, bone density distribution in the LM remains unclear.Materials and Methods We investigated bone density distribution in the posterior wall of the LM. A total of 120 LMs were analyzed from the patients who underwent laminoplasty. The distribution of BMD defined by Hounsfield unit (HU) in the posterior wall of the LM was measured by CT osteoabsorptiometry. The posterior wall was divided into nine zones, which consisted of three columns (lateral, center, and medial) and three rows (cranial, center, and caudal). BMD in each zone was averaged and compared by zones and cervical levels.Results Overall mean ± standard deviation BMD was 1,092 ± 433 HU. Averaged BMD in the entire posterior wall was highest at C4 (1,365 ± 459 HU), second highest at C3 (1,239 ± 435 HU), and lower in the lower levels. BMD in the medial–center zone (1,357 ± 443 HU) was the highest in all zones. BMD in the medial–caudal region at C7 was only 59% of the highest BMD in the medial–center region at C4.Conclusion The medial–center to the cranial region was most suitable for miniscrew fixation for laminoplasty. These biomechanical findings would be useful in the preoperative planning of laminoplasty especially for the determination of the LM screw entry points and in the design of laminoplasty implants.
Keywords: bone mineral density; lateral mass; osteoabsorptiometry; screw loosening